Clinical Features of Depression in Outpatients With and Without Co-Occurring General Medical Conditions in STAR*D: Confirmatory Analysis - Yates, William R. (Physicians Postgraduate Press, Inc., 2007)
Background: Concurrent medical comorbidity influences the accurate diagnosis and treatment of major depressive disorder (MDD). Objective: The objective of this study was to validate previous findings from the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study using a confirmation analysis in a previously unanalyzed cohort. Design: Baseline cross-sectional case-control study of patients enrolling in a prospective randomized multistage treatment study of nonpsychotic MDD. Setting: Fourteen regional U.S. centers representing 18 primary care and 23 psychiatric practices. Participants: 2541 outpatients with DSM-IV nonpsychotic MDD. Measurements: Sociodemographic status, medical illness ratings, psychiatric status, quality of life, and DSM-IV depression symptom ratings. Results: The prevalence of significant general medical comorbidity in this population was 50.0% (95% CI = 48.1% to 52.0%), consistent with findings reported for the first cohort. Concurrent significant medical comorbidity was associated with older age, lower income, unemployment, limited education, and longer duration of index depressive episode. The group with significant medical comorbidity reported higher rates of somatic symptoms, gastrointestinal symptoms, sympathetic arousal, and leaden paralysis. These results were generally consistent between the 2 cohorts from STAR*D. Conclusions: Major depressive disorder with concurrent general medical conditions is associated with a specific sociodemographic profile and pattern of depressive symptoms. This association has implications for diagnosis and clinical care.